Can Rationing through Inconvenience Be Ethical? - Eyal, Nir (The Hastings Center report, 2018)
In this article, we provide a comprehensive analysis and a normative assessment of rationing through inconvenience as a form of rationing. By “rationing through inconvenience” in the health sphere, we refer to a nonfinancial burden (the inconvenience) that is either intended to cause or has the effect of causing patients or clinicians to choose an option for health-related consumption that is preferred by the health system for its fairness, efficiency, or other distributive desiderata beyond assisting the immediate patient. We argue that under certain conditions, rationing through inconvenience may turn out to serve as a legitimate and, compared to direct rationing, even a preferable tool for rationing; we propose a research agenda to identify more precisely when that might be the case and when, alternatively, rationing through inconvenience remains ethically undesirable. After defining and illustrating rationing through inconvenience, we turn to its moral advantages and disadvantages over other rationing methods. We take it as a starting assumption that rationing, understood as scarce-resource prioritization, is inevitable and, in a society that has goals beyond optimizing health care for individual patients—such as improving societal health care, education, or overall welfare—prudent and fair.